Peran Program Magang Kependidikan III terhadap Penguasaan Technological Pedagogical Vocational Knowledge pada Mahasiswa Pendidikan Teknik Bangunan Universitas Sebelas Maret - Nabila Khairuni; Anis Rahmawati; Kundari Rahmawati (Arus Jurnal Pendidikan, 2022)
The research method uses a mixed method with sequential exploratory designs. This method combines quantitative and qualitative methods to obtain more effective and objective data. The goal is to know the perspective on the role of the Education Internship III program on the development of TPVK mastery, and the establishment of the TPVK framework during the Education Internship III. The results of this study are, student perception of the role of the Education Internship III program in mastery development, namely starting from setting the objectives of the internship program, setting a learning plan, and recognizing the classroom environment during the Internship process. Students of Building Engineering Education (PTB) UNS apply the TPVK framework in all learning activities during the Educational Internship Program III. Inappropriate use of technology makes it difficult for students to interact and hinders understanding of the material during learning. Some of the student internship activities (prospective pre-service teachers) are influenced by the guidance of the mentoring teacher.